Decreased arterial compliance assessed by aortic pulse wave velocity is an important parameter for monitoring of blood pressure in patients with chronic inflammatory diseases - H. Yilmaz Ak; Y. Ozsahin; N. Baskurt Aladag; F. Gencoglu; B. Sahin Yildiz; I. Haberal; A. Ozan Koyuncu; M. Yildiz (Российский кардиологический журнал, 2020)
Aim. Patients with chronic inflammatory diseases (CID), such as rheumatoid arthritis (RA) and familial Mediterranean fever (FMF) are more likely to have higher risk of cardiac events. Pulse wave velocity (PWV) can be used to measure the aortic dis-tensibility and it is known as inversely related to the arterial compliance. Increased aortic stiffness which is assessed by PWV, is seem to be associated with arterial blood pressure. In this study, we investigated the arterial compliance by PWV in patients with CID including RA and FMF.Material and methods. We studied 25 patients with RA, 33 patients with FMF and 31 healthy subjects without a history of any cardiovascular risk factors such as hypertension, diabetes mellitus, hyperlipidaemia (89 subjects in total). We measured the arterial compliance by automatic carotid-femoral (aortic) PWV using Complior Colson (France) device. PWV (m/s) = distance (m)/transit time(s).Results. It is seen that, patients with CID have higher carotid-femoral (aortic) PWV (8,76±2,09 vs 8,07±0,94 m/s) compared to control groups (p=0,03). There were significant correlations between PWV and age, body-mass index, systolic blood pressure, diastolic blood pressure and mean blood pressure. (p<0,001, r=0,65; p<0,001, r=0,36; p<0,001, r=0,42; p<0,001, r=0,46; p<0,001, r=0,48, respectively).Conclusion. Arterial compliance, which is assessed by carotid-femoral (aortic) PWV, is decreased in patients with CID such as RA and FMF when it is compared to healthy control group.